Buiness Practice in Ukraine 2019 Ukrainian business and economic outlook: a growth detected - Vakulenko, Veronika (Nord universitet, 2020)
Written in the manner of a scientific diary, this report summarizes the study trip to the capital of Ukraine, the city of Kyiv, made by the group of Master of Science students from Management Control specialization at the Nord University Business School, Bodø, Norway. The visit took place between 21 and 28 September 2019.